Evaluation of the resistance of american hybrids of citrus rootstocks to root infection by Phytophthora citrophthora (inoculation test on laboratory seedlings) - Vasconcellos, Hélio de Oliveira; Pereira, Joaquim R.; Drummond, Octávio Almeida; Cunha Filho, Lamartine Antonio da (Pesquisa Agropecuaria Brasileira, 2014)
Seedlings of several hybrids of citrus rootstocks of various crosses between Cleopatra mandarin x trifoliata Swingle; Cleopatra mandarin x Citrange carrizo; Swingle x C.E.S. rough lemon; and Sunki mandarin x trifoliata Swingle, introduced from the Dates and Citrus Station-Indio-California-U.S.A., were tested in laboratory for resistance to Phytophthora citrophthora. They were planted individually in small cylinders, with sand washed and sterilized at 127°C for two hours. One hundred and twenty days after planting, their intact roots systems were exposed to a suspension of zoospores. After 24 days incubation, the roots of each seedling were treated with 2, 3, 5 triphenyl tetrazolium chloride to identify the proportion of injured roots. The statistical plan was undesigned. There were no significant statistical differences among the treatments (hybrids). However, hybrids of Cleopatra mandarin x trifoliata Swingle 63-206; Cleopatra mandarin x trifoliata English 63-242; Cleopatra mandarin x Citrange carrizo 63-224, 63-227; and hybrids of Sunki mandarin x trifoliata Swingle 63-308, showed the smallest average of lateral roots infected by this pathogen. Seedlings of rangpur lime, used in the same test, showed high susceptibility to the pathogen, with infection of 80% to 100% in the lateral roots.